2017
DOI: 10.1186/s12913-017-2177-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between structure, process and outcome to assess quality of integrated chronic disease management in a rural South African setting: applying a structural equation model

Abstract: BackgroundSouth Africa faces a complex dual burden of chronic communicable and non-communicable diseases (NCDs). In response, the Integrated Chronic Disease Management (ICDM) model was initiated in primary health care (PHC) facilities in 2011 to leverage the HIV/ART programme to scale-up services for NCDs, achieve optimal patient health outcomes and improve the quality of medical care. However, little is known about the quality of care in the ICDM model. The objectives of this study were to: i) assess patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 30 publications
0
82
3
4
Order By: Relevance
“…The structure represents the conditions under which care is provided, the process represents the activities that constitute healthcare and the outcome represents the changes in the health status 18. It is suggested that good outcome is a result of a structure that promotes a good process,19 and that any efforts to improve the approaches in the triad must be seen in the light of care and needs of the patients 20. In the ECHO model, the outcomes of medical care are classified along three general dimensions: clinical, economic and humanistic 21.…”
Section: Introductionmentioning
confidence: 99%
“…The structure represents the conditions under which care is provided, the process represents the activities that constitute healthcare and the outcome represents the changes in the health status 18. It is suggested that good outcome is a result of a structure that promotes a good process,19 and that any efforts to improve the approaches in the triad must be seen in the light of care and needs of the patients 20. In the ECHO model, the outcomes of medical care are classified along three general dimensions: clinical, economic and humanistic 21.…”
Section: Introductionmentioning
confidence: 99%
“…This qualitative research is a case study of implementation of an ICDM model in PHC facilities and their catchment communities, and a part of a broader mixed methods research project which evaluated the quality of care in the ICDM model (15) in the study setting. The study population consisted of clients 18 years and above being managed for HIV, hypertension and diabetes in the seven PHCs in the sub-district.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Patients diagnosed with and being managed in the health facilities for HIV, hypertension, and diabetes were eligible to participate in the study. Inclusion criteria were being on treatment six months before the ICDM model was implemented, participating in health facility exit quantitative interviews on quality of the ICDM model of care commenced in June 2013 (15) and willingness to participate in the current Focus Group Discussions (FGDs). The managers of the seven health facilities in the district were purposively selected for the In-depth Interviews (IDIs) based on their depth of experience.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have focused on measuring health outcomes among the elderly that may be attributed to the implementation of IC. [14][15][16][17][18][19][20][21][22][23][24] Furthermore, it remains unclear from that literature the direction of effect, if any, of IC on hospital e ciency. Some studies demonstrated that integrated partnerships and a coordinated continuum of services dedicated to the treatment of specialized diseases or a de ned population may improve hospital e ciency.…”
mentioning
confidence: 99%